PENGEMBANGAN PRODUK FUNITUR ROTAN INDUSTRI SKALA USAHA KECIL DI DESA TRANGSAN PASCA PANDEMI COVID - 19: Product Development Of Industrial Rattan Furniture Small Business Scale In Trangsan Post-Covid Pandemic - Bambang Kartono Kurniawan; Gihon Nugrahadi; Ira Samri; Dyah Ayu Sekarningrum (Jurnal Dimensi Seni Rupa dan Desain, 2024)
The export-based rattan industry plays an important role for the country's foreign exchange, one of which is the export of rattan products has become the main source of income for the community in Trangsan Village, Sukoharjo Regency. However, small-scale rattan industry producers still have many limitations in developing product design in their companies. Most of the rattan industry in Trangsan Village still produces its products based on the demand of global market buyers, and the quality is determined by the buyer. This research focuses on the analysis of furniture design for the export market in Trangsan Village. The purpose of the research is to determine the impact of the post-Covid-19 Pandemic on the design development process for export rattan furniture products and how design plays a role in product innovation. This research uses the method of literature study and field observation with a qualitative descriptive approach. The results of the research show that rattan furniture manufacturers still have obstacles in developing designs. This research is expected to open opportunities for further research, contributing to the development of design innovation.